Devil Continues to Wear “Counterfeit” Prada: A Tale of Two Cities - Teah, Min; Phau, Ian; Huang, Y. (Emerald Group Publishing Limited, 2015)
Purpose – This paper aims to examine the influence of social and personality factors on attitudes towards counterfeiting of luxury brands and purchase intention between China Chinese and Taiwan Chinese consumers. Design/methodology/approach – Data collection was conducted using a mall intercept approach in downtown Shanghai and Taipei. A self-administered questionnaire was developed and back-translated from English to Chinese and distributed. Structural equation modelling in LISREL was used to analyze the data. Findings – It was found that collectivism has a positive relationship with attitudes towards counterfeiting of luxury brands for the China Chinese but not for the Taiwan Chinese. Personal gratification was found to have a negative relationship with attitudes towards counterfeiting of luxury brands for the Taiwan Chinese consumers. Integrity and status consumption were found to have a positive relationship with attitudes towards counterfeiting of luxury brands for both the China Chinese and Taiwan Chinese consumers. Research limitations/implications – The findings are limited to comparison between China Chinese from Shanghai and Taiwan Chinese from Taipei; therefore, the results may not be generalizable across all Chinese consumers or international consumers. In addition, only luxury brands were examined in this paper. Future studies would need to address other contexts or specific product categories. Practical implications – This paper presents findings from two Chinese cities. The consumers may be from the same region; however, it is found from the study that they pose different attitudes and purchase intentions towards counterfeits of luxury brands. Therefore, the insights from this paper provide a deeper understanding into the differences between Chinese consumers and implications for practitioners, academics and policy makers. Originality/value – Majority of the cross-national studies are often compared between the so-called Western or Eastern countries. This paper examined counterfeiting from China (which is deemed as one of the largest manufacturers of counterfeits) and Taiwan (which was one of the largest counterfeiters decades ago). This provides insights into the development and differences between regional consumers and their attitudes towards counterfeits of luxury brands.